Studies on the Anticonvulsant Activity and Influence on GABA-ergic Neurotransmission of 1,2,4-Triazole-3-thione- Based Compounds - Tomasz Plech; Barbara Kaproń; Jarogniew J. Łuszczki; Monika Wujec; Agata Paneth; Agata Siwek; Marcin Kołaczkowski; Maria Żołnierek; Gabriel Nowak (Molecules, 2014)
The anticonvulsant activity of several 1,2,4-triazole-3-thione derivatives on mouse maximal electroshock-induced seizures was tested in this study. Characteristic features of all active compounds were rapid onset of action and long lasting effect. Structure-activity observations showed that the probability of obtaining compounds exerting anticonvulsant activity was much higher when at least one of the phenyl rings attached to 1,2,4-triazole nucleus had a substituent at the para position. The obtained results, moreover, permit us to conclude that despite the structural similarity of loreclezole (second-generation anticonvulsant drug) and the titled compounds, their anticonvulsant activity is achieved via completely different molecular mechanisms.